2013
DOI: 10.1530/joe-13-0089
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transfer of methimazole and effects on thyroid hormone availability in embryonic tissues

Abstract: Methimazole (MMI) is an anti-thyroid drug used in the treatment of chronic hyperthyroidism. There is, however, some debate about its use during pregnancy as MMI is known to cross the mammalian placenta and reach the developing foetus. A similar problem occurs in birds, where MMI is deposited in the egg and taken up by the developing embryo. To investigate whether maternally derived MMI can have detrimental effects on embryonic development, we treated laying hens with MMI (0.03% in drinking water) and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 44 publications
2
42
2
Order By: Relevance
“…In mammals and fish maternal thyroid hormones are crucial for normal growth, development and even survival (reviewed by Power et al , Patel et al ). The avian embryo possesses thyroid hormone receptors before starting its own thyroid hormone production (Geysens et al , Van Herck et al , ). Furthermore, experimental elevation of thyroid hormones increased growth and hatching speed in quail and chicken (Wilson and McNabb ) and body mass in pigeons and great tits Parus major (Hsu et al pers.…”
mentioning
confidence: 99%
“…In mammals and fish maternal thyroid hormones are crucial for normal growth, development and even survival (reviewed by Power et al , Patel et al ). The avian embryo possesses thyroid hormone receptors before starting its own thyroid hormone production (Geysens et al , Van Herck et al , ). Furthermore, experimental elevation of thyroid hormones increased growth and hatching speed in quail and chicken (Wilson and McNabb ) and body mass in pigeons and great tits Parus major (Hsu et al pers.…”
mentioning
confidence: 99%
“…A shortage of thyroid hormones during the pre-birth period will lead to irreversible damage to the brain and mental retardation [14]. Madeira et al (1991) reviewed the impacts of hyperthyroidism on the granular layer of the dentate gyrus of the hippocampus in mature male and female rats.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest state of hyperthyroidism is in the form of Graves' disease. Untreatedhyperthyroidism in pregnant mothers is associated with hyperthyroidism in embryos [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal thyroid hormones [THs;3,5, and thyroxine (T4)] show central roles in the fetal and neonatal development during the gestation and lactation periods (El-bakry et al, 2010;Ahmed, 2011Ahmed, , 2012aAhmed, ,b, 2013Ahmed, , 2014Ahmed, , 2015aAhmed, -c, 2016aAhmed, -d, 2017aAhmed, -v, 2018aAhmed et al, 2008;2013a,b, 2014, 2015a,b, 2018aAhmed and Incerpi, 2013;Van Herck et al, 2013;El-Gareib, 2014, Incerpi et al, 2014;Candelotti et al, 2015;De Vito et al, 2015;El-Ghareeb et al, 2016;Ahmed and El-Gareib, 2017), in particular the hematopoietic cell proliferation and growth, the number of red blood cells (RBCs) and white blood cells (WBCs), and platelet counts (Grymuła et al, 2007;Kawa et al, 2010;Pascual and Aranda, 2013;Kandir and Keskin, 2016). In the bone marrow, Kendrick et al (2008) reported that THs can induce its cellular production.…”
Section: Short Communicationmentioning
confidence: 99%